Exploring the Anticancer Potential of Ferula assa-foetida Bioactive Compounds and Molecular Mechanisms in Breast Cancer Treatment - Korthiby Marcecal; Ramin Hazemi Hashemi; Niloofar Jafari; Mohammad Reza Karimi; Leila Pouran (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
Breast cancer is a major global health issue, with limited treatment options that often come with adverse side effects. Ferula assa-foetida, a medicinal plant known for its anti-inflammatory, antioxidant, and antimicrobial properties, has shown potential as an anticancer agent. This study investigates the anticancer effects of Ferula assa-foetida extracts on breast cancer cell lines (MCF-7 and T47D). The research identifies key bioactive compounds, such as ferulic acid and flavonoids, and explores their molecular mechanisms. In vitro assays, including cytotoxicity assays (MTT and Alamar Blue) and apoptosis detection (Annexin V/PI staining), were conducted to measure cell proliferation and apoptosis induction. Furthermore, PCR and Western blot analyses were used to examine the expression of apoptosis-related genes (p53, Bcl-2, and caspase-3). The results indicate that Ferula assa-foetida extracts significantly inhibit cell growth and induce apoptosis in breast cancer cells. This study provides insights into the potential of Ferula assa-foetida as a complementary treatment for breast cancer and supports further research to evaluate its clinical applicability.